Design and measurement results for cooperative spectrum sharing - Vivek Ashok Bohara (2011)
Scarcity of radio spectrum and inherent inefficiency of current spectrum allocation policies have spurred much research for alternative spectrum access techniques giving birth to the notion of cognitive radios.